2020
DOI: 10.1177/1059840520963621
|View full text |Cite
|
Sign up to set email alerts
|

School Nurse Job Descriptions in Urban Districts: Alignment With the Framework for 21st-Century School Nursing Practice

Abstract: It is recommended that every student has daily access to a school nurse and that school nurses work in alignment with the Framework for 21st-Century School Nursing Practice (Framework). Little is known about Framework alignment with school nursing practice. The purpose of this study is to describe the alignment between the Framework and school nurse job descriptions in large, urban school districts across the United States. Using content analysis, with a directed approach, researchers used the Framework to ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 8 publications
1
5
0
Order By: Relevance
“…Our finding showed that school nurses' highest educational needs concern ‘regulations on campus medical orders’ and ‘defining and addressing medication errors on campus’. This resonates with the findings of Reising and Cygan (2022) and Yu et al. (2023) which highlight the conflicts and stresses school nurses experience when providing direct services in schools, juggling their roles as school nurses and adhering to medical direct care standards.…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…Our finding showed that school nurses' highest educational needs concern ‘regulations on campus medical orders’ and ‘defining and addressing medication errors on campus’. This resonates with the findings of Reising and Cygan (2022) and Yu et al. (2023) which highlight the conflicts and stresses school nurses experience when providing direct services in schools, juggling their roles as school nurses and adhering to medical direct care standards.…”
Section: Discussionsupporting
confidence: 73%
“…In non‐medical settings, school nurses are expected to serve as care coordinators and managers in terms of chronic disease management for students. However, a study by Reising and Cygan (2022) which focused on large urban areas revealed that the role most frequently described for school nurses is that of a direct care provider. Medication administration in schools is a form of direct care provided to students with chronic diseases that must adhere to the policies or regulations of countries or regions.…”
Section: Introductionmentioning
confidence: 99%
“…From the study of Reising and colleagues (Reising & Cygan, 2022), it emerges that school nurses mainly practice activities related to the key principles of care coordination and community/public health, compared to other activities (leadership and quality improvement), which allows us to reflect on how nursing skills in the US need to be aligned with the Framework aforementioned. The studies included showed that in the US there is a problem related to the number of active school nurses there are 96,000 full-time nurses, but not all schools can find qualified personnel or pay professionals: 25% of schools do not have school nurses (Trefry, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…However, school nurses often report difficulty in incorporating the Framework into their daily practice (Maughan et al, 2016;Best et al, 2017). This has led to the call for practical tools to guide school nurses in practicing alignment with the Framework (Best et al, 2017;Reising & Cygan, 2020). Specifically, researchers recognized the need for tools that focus on population-level evidence-based practice (Davis et al, 2019).…”
Section: Discussionmentioning
confidence: 99%